Psycho-educational program for high school females - Perla Caridad López Hernández; Laura López Angulo; Eneida Bravo Polanco; Carmen Benítez Cabrera; Lisbet Cepero Águila; Rafael Luis Pino Pich (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Introduction: sex education provides knowledge, values and attitudes that both, men and women need to live with dignity and develop fully and happily. Objective: to determine the usefulness of applying a psycho-educational program on female sexuality in high school. Methods: a quasi-experimental study conducted between September 2007 and June 2008, based on a sample composed of 180 ninth grade females living in Cumanayagua's urban area. Variables analyzed: adolescents knowledge on sex-related risks, sexually transmitted infections and contraceptives. They were all analyzed before and after applying the psycho-educational program. Results: after applying the psycho-educational program, knowledge standard on the right time to begin with sexual intercourses (18% to 71%), the risk of pregnancy at first sexual intercourse (37% to 75%) and the consequences of pregnancy and abortion in adolescence (from 57% to 71%) increased. Regarding STI's, there were also improvements (from 27% to 75%), and as to the ideal contraceptive the features raised from 0% to 92%. Conclusions: The psycho-educational program proved to be effective in students and raised the knowledge standard on these fundamental aspects of sex education.